Exhibiting Evidence: A Case Study - Nicholls, Catherine (Archivaria, 2003)
This article presents criteria for successful exhibition activities. It then introduces a contextualized case study of an Australian archive exhibition (the National Archives of Australia’s “Between Two Worlds” Exhibition) in order to understand the components that contribute towards successful exhibition activities. The issue of whether exhibitions should be valued as peripheral or core activities in an archive program is also addressed. RÉSUMÉ Cet article présente des critères de réussite pour les activités d’expositions. L’auteure examine ensuite le cas de l’exposition des Archives nationales d’Australie « Between Two Worlds » afin de comprendre les éléments qui ont contribué au succès des activités de cette exposition. Elle soulève enfin la question de savoir si les expositions doivent être au centre ou à la périphérie des activités des centres d’archives.